A numerical investigation of the flows in and around clustered module plug nozzles - Perigo, D. A. (Cranfield University, 2001)
This thesis aims to make advances in the accurate simulation of the ows in and around clustered module plug nozzles. The resulting simulations presented in this thesis are, as far as can be ascertained from available data, the most detailed to date in Europe. A comparison is made with results from other sources for clarication of this point. In the process of producing these solutions, two ow solvers have been developed. NSAXIMB is a general 2D multi-block ow solver,developed by the author, for the axisymmetric, Reynolds averaged Navier-Stokes equations. It was developed to allow simulation of axisymmetic plug nozzle congurations and the investigation of the effects of turbulence modelling on such ows. MERLIN is a general 3D, implicit, multi-block ow solver again for the RANS equations. MERLIN was developed by the Centre for Computational uid Dynamic at Craneld. Signicant input from this work has included a large portion of the structure of the mean ow solver and the extension of the advanced two equation turbulence modelling, incorporated in NSAX- IMB, to three dimensions. Of the turbulence models investigated the zonal models of Menter prove to be most effective in reproducing experimental results. These models out perform a more advanced non-linear eddy viscosity formulation, based on the work of Abid. In an effort to improve solution accuracy, grid adaptation software, based on node redistribution techniques has been developed for use in conjunction with the 3D ow solver. This work is demonstrated in conjunction with a basic test case before application to the clustered module plug nozzle conguration. Results for the complex block topology adopted in the 3D test case are shown to cause the adaptation process to fail. Further, it is shown that such a process may not be generalised for arbitrary topologies.